Synthesis and Antimicrobial Activity of Some Novel Schiff Bases Containing 1,2,4-Triazole-3-thione - KAYMAKÇIOĞLU, BEDİA (WWW PUBL PTE, 2010)
A series of Schiff bases (4a-j) were prepared by reacting 4-amino-5-(1-phenylethyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione and substituted aromatic aldehydes. The chemical structures were confirmed by means of UV, (1)H NMR, IR, MS(API-ES) spectral data and elemental analysis. All the synthesized compounds were screened for their antimicrobial activity. Among the tested compounds, Schiff bases with 4-OH and 4-NO(2) substituent exhibited remarkable antimicrobial activity against all the tested microorganism.
Keywords: 1,2,4-Triazole-3-thione; Schiff bases; Antimicrobial activity; MANNICH-BASES; ANTICANCER ACTIVITY; DERIVATIVES; AGENTS; ACID; DESIGN; ANTIBACTERIAL; ANTIFUNGAL; ISATIN